Effectiveness Of Halal Certification Assistance In Self-Declare Pathway For Micro And Small Enterprises In Surabaya - Filzah Wafiyah; Moh Farih Fahmi; Muhammad Ufuqul Mubin (Universitas Islam Darul 'ulum Lamongan, 2024)
The Indonesian government effort through the Halal Product Guarantee Organizing Agency, launched the Halal certification program, a self-declaration program specifically for micro and small businesses. The halal certification program involves a Halal Product Process Assistant who is responsible for assisting business proprietors in submitting product halal statements. This research aims to analyze the effectiveness of halal certification assistance to micro and small enterprises in self declare pathway at Surabaya. This research uses a qualitative method with a phenomenological approach. Data collection techniques by conducting in-depth interviews, observation and documentation with primary and secondary data sources. The research results show that halal sertification assistance has contributed to the issuance of a number of halal certificates for micro and small enterprises in Surabaya. Halal certification assistance to business proprietors at Surabaya has been effective in the aspect of achieving goals and integration, but less so in the aspect of adaptation.